SCIENTIFIC-THEORETICAL BASIS OF THE PROBLEM OF DETERMINING AGGRESSION IN PERSON IN PSYCHOLOGY (Eureka Journal of Humanities and Social Research, 2025)
The article explores the psychological essence of aggression, focusing on its passive and active forms as well as their manifestation in social, emotional, and cognitive processes. It analyzes A.G. Bass’s and S. Feshbach’s classifications of aggression, highlighting differences in motivation and purpose. The study also examines the open and hidden expressions of aggressive behavior in family and social relations, their connection to criminal acts, and their impact on individual psychology through practical examples.
Keywords: Aggression, passive aggression, active aggression, personality behavior, hostility, psychological analysis, criminality.